Antimicrobial efficacy of the combination of chlorhexidine digluconate and dexpanthenol - Kramer, Axel; Assadian, Ojan; Koburger-Janssen, Torsten (German Medical Science GMS Publishing House, 2016)
Objective: The objective of this standardised experimental study was to investigate the antimicrobial efficacy of the combination of chlorhexidine digluconate (CHX) and the anti-inflammatory pro-vitamin dexpanthenol, which stimulates wound-healing, in the form of Bepanthen Antiseptic Wound Cream, in order to rule out possible antagonistic combination effects of CHX and the alcohol analogue of pantothenic acid (vitamin B5) dexpanthenol.Method: Testing was carried out using the quantitative suspension test at conditions simulating wound bio-burden. Test strains included (ATCC 10541) and (ATCC 10231) in accordance with the standard methods of the German Hygiene and Microbiology Society with the following three organic challenges: i) cell culture medium MEM with Earle's salts, L-glutamine and 10% foetal calf serum (CCM); ii) 10% sheep's blood; iii) or a mixture of 4.5% albumin, 4.5% sheep's blood and 1% mucin. For methodological reasons, the wound cream was tested as a 55% dilution, prepared with 1% Tween 80 (equivalent to a content of 0.275% CHX instead of 0.5% as in the original preparation). CHX 0.275% was tested as control in an aqueous solution and in 1% Tween 80. Additionally, 1% Tween 80 was tested in order to rule out an interfering effect of the dilution medium. A combn of 3% Tween 80, 3% saponin, 0.1% histidine, 0.3% lecithin, 0.5% Na-thiosulphate and 1% ether sulphate was identified as the most appropriate neutraliser during the experiments.Results: Exposed to CCM or 10% sheep's blood, the tested wound cream fulfilled the requirements for a wound antiseptic against both test species with ≥3 log reduction at 10 minutes. Even at the the worst-case challenge test with 4.5% albumin, 4.5% sheep's blood and 1% mucin, the requirement for a ≥3 log reduction was met after 24 hours of exposure. Interestingly, the aqueous solution of 0.275% CHX tested as control did not achieve the antimicrobial efficacy of the combination of CHX and 5% dexpanthenol. 1% Tween 80 was ineffective against both test species.Conclusion: Bepanthen Antiseptic Wound Cream achieves the bactericidal and fungicidal efficacy required for a wound antiseptic under three different challenges, despite dilution to 55% of the original preparation. So far, the addition of dexpanthenol was intended to support wound healing. However, our results indicate that the antiseptic efficacy of CHX is synergistically increased by adding 5% dexpanthenol. Acknowledging the antimicrobial and residual efficacy of CHX, and bearing in the mind the contraindications to CHX (allergy and anaphylaxis), the tested wound cream should be regarded as better suitable to be used as wound antiseptic than preparations on basis of CHX alone.